AI Empowered Virtual Reality Integrated Systems for Sleep Stage Classification and Quality Enhancement - Jing Huang; Lifeng Ren; Lifang Feng; Fan Yang; Lingfan Yang; Ke Yan (IEEE, 2022)
Insomnia is a common public health problem and an open biomedical research topic. Insomnia results in various health problems, including memory decline, decreases concentration and weakens problem-solving ability. The insufficient sleep also leads to skin ageing, heart disease, high blood pressure, arrhythmia and stroke. While it remains as a global health concern, sleep quality improvement using modern technologies, such as machine learning, classification technologies, virtual reality (VR), becomes an open and hot research problem. These modern technologies offer new curing solutions under certain conditions. In this paper, we present a sleeping-aid system with a single-channel electroencephalogram (EEG) sleep stage classification algorithm to improve the sleep quality. The sleeping-aid system promotes machine learning integrated VR and multimedia technology for sleep improvement. Ninety participants were invited to test on three different systems with 3D VR, 2D video, and music only. An adequate stimulus of audio-vision can be a complement of the drug treatment. The experimental results showed that the proposed method demonstrated superior performance over existing methods.